ESSEX: Equipping Sparse Solvers for Exascale - Hager, Georg; Kreutzer, Moritz; Shahzad, Faisal; Wellein, Gerhard; et al. (Euro-Par 2014: Parallel Processing Workshops, 2014)
The ESSEX project investigates computational issues arising at exascale for large-scale sparse eigenvalue problems and develops programming concepts and numerical methods for their solution. The project pursues a coherent co-design of all software layers where a holistic performance engineering process guides code development across the classic boundaries of application, numerical method, and basic kernel library. Within ESSEX the numerical methods cover widely applicable solvers such as classic Krylov, Jacobi-Davidson, or the recent FEAST methods, as well as domain-specific iterative schemes relevant for the ESSEX quantum physics application. This report introduces the project structure and presents selected results which demonstrate the potential impact of ESSEX for efficient sparse solvers on highly scalable heterogeneous supercomputers.
UnivIS-Import:2015-04-20:Pub.2014.tech.IMMD.phleir.essexe